Pengaruh Kualitas Pelayanan dan Promosi Digital Terhadap Peningkatan Laba Cafe Four Queens Palangka Raya - Chrystin Enjellia Purba; Windy Utami Putri; Grace Evelina Buji; Alexandro, Rinto (Journal Pendidikan Ilmu Pengetahuan Sosial, 2024)
The service quality and digital promotion of Café Four Queens has recently experienced a lack of attention from business owners because the café owner's focus is divided between studying and working, resulting in the quality of service still not satisfying customers, because there are still order errors and delays in serving consumer orders. Likewise, the digital promotions carried out by Café Four Queens have recently not attracted potential consumers. This can be seen from the decline in viewers for digital promotions carried out on the Four Queens Instagram account. This research aims to determine the influence of service quality and digital promotion on increasing profits at Café Four Queens Palangka Raya. And based on the results of data analysis. Normality Test, Multicollinearity Test, Hesterocedasticity Test, Determination Test, Simultaneous Test (F), Partial Test (T). The results of this research, the independent variables in this research, namely service quality and digital promotion, contributed 69.8% to the dependent variable and the remaining 31.2% was influenced by other variables and simultaneous hypothesis testing (F) obtained a value based on SPSS calculations of 60.046 where fcount > ftable is 60.046 > 3.23 and the significance value is 0.000 < 0.05. Thus, it can be concluded that there is a positive and significant relationship between service quality and digital promotion on increasing profits at Café Four Queens, Palangka Raya City